ENT Board Prep : high yield Review for the otolaryngology in-service and board exams - Patel, Zara; Lin, Fred (Springer New York, 2014)
ENT Board Prep is a high-yield review that is an ideal study guide for the ENT in-service and board exams. While other review guides are low yield or more of a textbook, this is quick, concise, and easy-to-use, providing everything you need to know in a easy to digest format. ENT Board Prep offers review on sections such as cancer, ear, sinus, plastics, sleep, and laryngology, as well as case studies useful for studying for the oral board exams. Written and edited by leaders in the field, this book aims to serve future residents and fellows in those crucial weeks leading up to the ENT board exam.